DETEKSI DINI ANEMIA SEBAGAI UPAYA PREVENTIF PENCEGAHAN ANEMIA PADA REMAJA - Lelly Aprilia Vidayati; Alis Nurdiana; Norma Farizah Fahmi (STIKES NGUDIA HUSADA MADURA, 2020)
Anemia is a condition of iron deficiency, where anemia can attack anyone, including teenagers who are still at an early age. Anemia is more common in adolescent girls than adolescent boys. The phenomenon obtained through interviews with BK teachers at SMPN 02 Bangkalan is that 5% of young women tend to go home on the first day of menstruation because they feel dizzy and have dysmenorrhea pain and 13% rest in the UKS room, especially on the first day of menstruation. Seeing the magnitude of the impact caused by anemia, especially in adolescents, it is very important to do promotive and preventive efforts as well as early detection of anemia in adolescents considering that young women are prospective mothers who will give birth to the next generation and to minimize the risk of bleeding due to anemia during childbirth.